Effect of Lactic Acid and Irradiation on the Shelf Stability Characteristics of Hurdle Processed Chicken Legs - Jayathilakan, K.; Sultana, Khudsia; Radhakrishna, K.; Bawa, A.S. (International Journal of Poultry Science, 2009)
Hurdle processed chicken legs were subjected for irradiation at 1 and 2 KGy dosage levels after treatment with lactic acid (1 and 2%) to study the effect of irradiation and lactic acid on the shelf stability of the product. The products initially and during storage at 5oC were evaluated for its oxidative rancidity profile in terms of Thiobarbituric Acid Reactive Substances (TBARS), Total carbonyls and non-heme iron values. Lipid oxidation increased with reference to irradiation dosage and there was a significant difference (p<0.05) between control, 1 KGy and 2 KGy samples (without lactic acid) after 6 months of storage. Incorporation of lactic acid at 2% levels significantly reduced (p<0.05) the TBARS, total carbonyls and non-heme iron values. Hurdle processed chicken legs irradiated at 2KGy with 2% lactic acid exhibited good sensory attributes after 6 months of storage having an overall acceptability score of 7.84±0.31 on a 9 point hedonic scale. The total fatty acid profile by gas chromatography revealed a significant reduction (p<0.05) in unsaturated fatty acids in irradiated samples but saturated fatty acids remained unaffected. The values for non irradiated samples during storage did not differ significantly (p>0.05). Microbiological profile of the product showed a 3 log reduction in SPC and 2 log reduction in Yeasts and molds by employing 2KGy irradiation dosage and pathogens were also absent.